Dachas and food democracy—What makes a (good) food citizen? - Pungas, Lilian (Frontiers in Sustainable Food Systems, 2023)
Against the backdrop of multiple crises within—and due to—the current industrial agri-food system, food is a highly political issue. As calls for food sovereignty grow louder and the war in Ukraine exposes the fragility of global food systems, the concept of food democracy calls on all (food) citizens to engage in a democratic and collective struggle for socially just and environmentally friendly food systems. To date, “Western” examples of food democracy and formal political procedures of civil society have dominated scholarship, ignoring the self-organized, low-key, and informal political activities around food in the post-socialist East. In this article, we shed light on the aspects of food democracy within Food Self-Provisioning (FSP) practices in Eastern Estonia, which is our case study. Our empirical data is based on semi-structured interviews conducted in 2019–2021 with 27 gardeners on their so-called dachas—a Russian term for a plot of land with a seasonal allotment house used primarily for food production. The analysis focuses on the food-, farming-, and nutrition-related attitudes and practices of the gardeners, as well as the multitude of collective endeavors to improve food systems. Despite the precarious socio-economic and political status of the gardeners, we identified a variety of subtle, informal, and mundane forms of democratic practices and everyday resistance. We investigate the interplay of these aspects along the three dimensions of food democracy (input, throughput, output). On the one hand, FSP on Eastern Estonian dachas encompasses essential characteristics of the mainly “Western” concept of food democracy, allowing access to and participation in agricultural production while preserving (re)productive nature in the future. On the other hand, we caution against excessive optimism and romanticization of such local food communities, as they tend to remain exceptions and risk extinction or displacement if they are not valorized and reshaped through public discourse. We conclude with a plea for building and strengthening alliances between the marginalized elderly rural food producers and the more youthful urban food activists to achieve more democratic, just, and ecologically sound food systems.